Pelatihan Public Speaking bagi Siswa SMA Muhammadiyah 5 Palembang: Pengabdian - Nur Azizah; Rina Dwi Wulandari; Achmad Tasmi; Sayid Habiburrahman (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Public speaking is a fundamental soft skill for high school students to face academic challenges and future career demands in the 21st century. However, based on the preliminary analysis at SMA Muhammadiyah 5 Palembang, students face significant obstacles in the form of glossophobia or excessive anxiety when speaking in public. This community service activity aims to improve students' self-confidence and effective communication skills through intensive training. The method employed is Participatory Action Research (PAR), which involves collaborative problem mapping, action planning, training implementation, and reflection. The training utilizes a participatory learning approach with role-playing techniques to create a psychologically safe environment for students. The results showed a significant increase in students' self-confidence and understanding of communication techniques, indicated by the increase in the average pre-test and post-test scores. This activity succeeded in transforming student passivity into active participation. It is recommended that the school establish a public speaking club as a follow-up plan to maintain the sustainability of students' skills.